Younger Age at Onset Is Associated With Worse Long-term Behavioral Outcomes in Anti-NMDA Receptor Encephalitis. Issue 5 (6th September 2022) - Yeshokumar, Anusha; Gordon-Lipkin, Eliza; Arenivas, Ana; Rosenfeld, Mark; Patterson, Kristina; Blum, Raia; Banwell, Brenda; Venkatesan, Arun; Lancaster, Eric; Panzer, Jessica; Probasco, John
Abstract : Background and Objectives: Anti-NMDA receptor encephalitis (anti-NMDARE) is one of the most common causes of encephalitis. It typically presents in adolescence and young adulthood, but little is known about its potential long-term consequences across the lifespan. Adaptive behavior describes an individual's ability to respond and adapt to environmental demands and unanticipated changes in daily routines. In this study, we evaluate the relationship between features from clinical presentation, including age, and long-term adaptive behavior in participants with anti-NMDARE. Methods: Cross-sectional informant-reported data were collected between 2017 and 2019 from 41 individuals/caregivers of individuals with anti-NMDARE treated at 3 major academic hospitals. Neurologic disability was assessed by record review using the modified Rankin Scale (mRS). Functional outcomes were assessed using the validated Adaptive Behavior Assessment System, Third Edition (ABAS-3). Results: The mean age at the time of study enrollment was 23.4 years (SD 17.0 years), and the mean time from symptom onset to study enrollment was 4.0 years. Seventeen participants were aged <12 years at symptom onset, 19 participants were aged 12–30 years, and 5 participants were aged >30 years. Mean ABAS-3 scores at study enrollment for all participants were in the average range (mean general adaptive composite standard score 92.5, SD 18.7). Individuals aged <12 years at symptom onset had lower mean ABAS-3 scores and were in the below average range compared with those aged 12–30 years at symptom onset, whose mean scores were in the average range (87 vs 99, p < 0.05). Similar differences were seen in 3 of the individual subscales (functional academics, health and safety, and self-care). There were no significant differences in mRS scores between age groups ( p > 0.05). Discussion: Although anti-NMDARE is associated with an overall favorable outcome, younger age at onset associates with worse long-term adaptive behavior despite no differences in neurologic disability. These findings suggest that the disease may have distinct consequences on the early developing brain. Future studies should evaluate behavioral recovery and quality of life after anti-NMDARE and identify additional factors associated with differential recovery.